Information, knowledge and innovation: contemporary brazilian production and united nations sustainable development goals - Úrsula Gomes Rosa Maruyama (Cuadernos Latinoamericanos de Administración, 2016)
is work aims to analyze recent Brazilian literature on innovation in the search for studies related to the United Nations’ ninth Sustainable Development Goal (SDG) Industry, Innovation and Infrastructure: "build resilient infrastructure, promote sustainable industrialization and foster innovation’. e theoretical framework on innovation is based on classic authors from the eld such as Freeman (1995); Lundvall (1985, 1996, 2009); Hippel (2007); Nelson and Winter (2002); Srivas and Sutz (2008). e paper is developed as a literature review with a comparative study to analyze data collected from a Brazilian journal on business and innovation: Revista de Administração e Inovação (RAI). Due to the topicality of the subject, the period between 2014 -2015 was chosen for the sample. During this time, 73 articles were published in ve numbers of RAI. Among them, 48 articles were selected according to the established criteria to determine the identication with the theme of SDG9 Industry, Innovation and Infrastructure. ese 48 articles were stratied and analyzed. e results indicate the need to stimulate research in the area of innovation in line with SDG9 approach.